Interdependence and asymmetries: Latin American ADRs and developed markets - Ana Carolina Costa Correa (FUCAPE Business School, 2018)
The ADRs market presented great growing importance in the last decades, specially for companies based on developing countries, such as those of Latin America. In this context, this research sought to detect and measure the interdependence phenomenon, comprising the returns and volatility spillovers and their asymmetries between the levels 2 and 3 ADRs of the main capital markets of Latin America (Brazil, Argentina, Chile and Mexico) and the developed ones (the United States, Japan, the United Kingdom and France), regarding the last financial crisis scope. This phenomenon was investigated considering both the daily returns of their market stock indices, such as those of the ADRs indices created in this study, from June 2008 to May, 2015, via VAR-MGARCH multivaried skewness models, with diagonal VECH representation. The main conclusion was that the ADR indices presented greater interdependence with the developed countries, compared to the analyzed Latin American equity markets.